Hydrodynamic cavitation in Stokes flow of anisotropic fluids - Tillmann Stieger (Nature Portfolio, 2017)
Cavitation is the formation of vapour bubbles within a liquid and is undesirable in many industrial applications. Here Stiegeret al. show how the anisotropic fluids influence this process in a nematic liquid crystal and find that orientational ordering of molecules can tune the onset of cavitation.